Three-Dimensional TiO2 Film Deposited by ALD on Porous Metallic Scaffold for 3D Li-Ion Micro-Batteries: A Road towards Ultra-High Capacity Electrode. Issue 4 (1st April 2022) - Hallot, Maxime; Boyaval, Christophe; Troadec, David; Huvé, Marielle; Karroubi, Lotfi Benali; Patnaik, Sai Gourang; Brousse, Thierry; Roussel, Pascal; Pech, David; Lethien, Christophe
Abstract : To power the next generation of miniaturized electronic devices, the energy storage capability of Li-ion micro-batteries has to be significantly improved and the fabrication of high performance 3D electrodes is mandatory. Here we show how to carefully match the design of efficient 3D scaffold based on metallic porous template with the deposition parameters of titanium dioxide films made from thermal Atomic Layer Deposition method for designing efficient 3D electrodes for Li-ion micro-batteries. A 3D electrode made from Pt porous scaffold coated with 150 nm-thick anatase TiO2 film reaches a high surface capacity value up to 1600 μ Ah.cm −2 at C/12 with a good cycling stability during 100 cycles.